'No one's ever said anything about sleep': A qualitative investigation into mothers' experiences of sleep in children with epilepsy. (6th January 2023) - Cook, Georgia; Gringras, Paul; Hiscock, Harriet; Pal, Deb K.; Wiggs, Luci
Abstract: Introduction: Sleep problems in children with epilepsy (CWE) are common. However, little is known about parental experiences and feelings about managing sleep in their CWE. To provide the most appropriate services' provision, it is essential that the lived experience of parents of this patient group and the issues and problems that they face in managing their child's sleep is understood. Method: In 2018, nine mothers of CWE (aged 5–15 years) were interviewed about their perceptions and experiences around their child's sleep, sleep problems and their management, the impact of sleep difficulties on the child and their family and available support. Results: Four themes were identified that represented the nature of the child's sleep problems, including settling and night‐waking issues, parasomnias and child anxiety around sleep. Seven themes represented mothers' experiences of managing their child's sleep and any associated problems, including the longstanding challenging nature of child sleep issues, management strategies adopted, challenges related to managing sleep over time, the link between sleep and seizures, the negative impact of poor sleep on daytime functioning, role of antiseizure medication and maternal concerns about child sleep. One theme represented the perceived lack of information, help and support available. Conclusions: Findings suggest there are unmet needs in supporting parents to deal with sleep, sleep problems and their management in CWE. Patient or Public Contribution: This individual study was conducted under the umbrella of the CASTLE research programme (see https://castlestudy.org.uk/ ). Parents who have lived experience of parenting a child with epilepsy were co‐applicants for the programme and were involved in the original conception, aims, design and funding application for the research programme (including the project reported in this paper) and advised on project design. Mothers of CWE who have lived experience of managing sleep and sleep problems in their child were participants who shared their experiences through the interviews, which formed the data of the current study.